2017
DOI: 10.1002/ange.201705017
|View full text |Cite
|
Sign up to set email alerts
|

A Rechargeable Li‐CO2 Battery with a Gel Polymer Electrolyte

Abstract: The utilization of CO 2 in Li-CO 2 batteries is attracting extensive attention. However,the poor rechargeability and lowapplied current density have remained the Achilles heel of this energy device.The gel polymer electrolyte (GPE), which is composed of apolymer matrix filled with tetraglymebased liquid electrolyte,w as used to fabricate ar echargeable Li-CO 2 battery with ac arbon nanotube-based gas electrode. The discharge product of Li 2 CO 3 formed in the GPE-based Li-CO 2 battery exhibits ap article-shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…However, pure carbon nanophases like Ketjenblack, CNT, and graphene commonly exhibit the energy efficiencies ranging from 60% to 65% using liquid electrolyte . If the safer quasi‐solid‐state polymer electrolyte was used in Li–CO 2 battery, the energy efficiency has already proved to be further decreased . For example, only 58% is recorded in our control sample, pristine CNT cloth (Figure d).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…However, pure carbon nanophases like Ketjenblack, CNT, and graphene commonly exhibit the energy efficiencies ranging from 60% to 65% using liquid electrolyte . If the safer quasi‐solid‐state polymer electrolyte was used in Li–CO 2 battery, the energy efficiency has already proved to be further decreased . For example, only 58% is recorded in our control sample, pristine CNT cloth (Figure d).…”
mentioning
confidence: 87%
“…Subsequently, Figure f compares CC@Mo 2 C NPs with some typical reported Li–CO 2 battery cathode materials in terms of various electrochemical properties. It is found that high specific capacity and low charge plateau have both been integrated into this CC@Mo 2 C NPs hybrid film and its energy efficiency outperforms that of all previous catalysts for Li–CO 2 batteries ever reported . The excellent electrochemical performance of CC@Mo 2 C NPs should be attributed to the significant advantages of this unique 0D/1D hybrid nanostructure as follows: first, 3D porous framework entangled by 1D CNTs supplies enough inner space for the deposition of discharge product, and thus opening more active sites to Li + and CO 2 gas instead of the electrode surface alone.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…They have an open cathode structure which can continuously admit O 2 from the surrounding atmosphere and reduce it to Li 2 O 2 during discharge, and can release O 2 from the reoxidation of Li 2 O 2 back to the atmosphere during charge. Analogous to Li–O 2 , rechargeable Li–CO 2 batteries have been experimentally demonstrated in recent years . They operate based on the redox chemistry of CO 2 , ideally following the equation 4Li + 3CO 2 ↔ 2Li 2 CO 3 + C with a theoretical energy density of 1876 Wh kg −1 .…”
mentioning
confidence: 99%
“…In particular, it is well known that the stable nature of Li 2 CO 3 inevitably induces dead space in the cathode side, which eventually causes decreased cycle ability and increased charge potential. In order to cope with this fatal issue, paradoxically, researchers have successfully proposed a Li-CO 2 cell and suggested the importance of its application as both a rechargeable secondary battery and CO 2 capture device to retard global warming 5,[15][16][17][18][19][20][21][22] . The proposed CO 2 reduction reaction (CO 2 RR) in the Li-CO 2 battery is based on the following electrochemical reaction: 4Li + + 3CO 2 + 4e − → 2Li 2 CO 3 + C (2.80 V vs. Li/Li + ) 5 .…”
mentioning
confidence: 99%